Kingdom of Lesotho : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Extension of the Arrangement and Rephasing of Disbursement. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
The Extended Credit Facility (ECF) program extended to Lesotho after a sharp fall in revenues remained broadly on track. Lesotho maintained positive growth supported by expansion of mining and construction. Fiscal consolidation efforts have helped to strengthen international reserves, despite weak diamond prices. Executive Directors welcomed the government's continued efforts to improve the business climate and promote private sector development. They also suggested the need to maintain fiscal consolidation efforts, while safeguarding priority social and growth-promoting capital spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet